Kebijakan Tata Niaga Obat di Indonesia: Kontroversi Sistem Distribusi dan Konsekuensi Kelembagaannya - Sumarto, Mulyadi (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2004)
Untuk keperluan lebih lanjut gunakan fasilitas Advance Search About Katalog Buku Laporan Penelitian Jurnal Home Berita Buku Tamu Forum Registrasi Inherent UGM Basic Search | Daftar Jurnal | Statistik Detail Hasil Pencarian Judul : Kebijakan Tata Niaga Obat Di Indonesia : Kontroversi Sistem Distribusi Dan Konsekuensi Kelembagaannya. Pengarang : Mulyadi Sumarto Jurnal : Jurnal Kebijakan dan Administrasi Publik 2004, VIII(1) Tahun : 2004 Summary / Kata Kunci : ABSTRACT Drug distribution is a multifaceted phenomenon. On one side it is a pure health phenomenon but on the other side it is loaded with political-economic drives.The mechanism distributing drug determines the eminence of health services. An appropriate rystem convinces people to get wide access consuming drug smarty. Interestingly, it involve huge amount of capital invested by private sector. The profit comes to corporations is shaped by the rystem. Thisfail urges corporations to work closer with the entities which able to support them politically. Rent seeking refers to the efforts of private sector obtaining political resource from polly maker. What have been done by the corporations has not only changed the polig makingprocess but also the decision taken byit).triciarzr pointing out drugs for their patients. The medical doctors choose drug is based on economic consideration rather than medical reasons. It deteriorates health services. Since the rystem of drugdistribution is rootingfor market, it puts people on a position in which unable empower them. The gstem causes the health services less accessibleforpeople.